Eco-critical Consciousness Meets Oppositional Consciousness: Reading Early Chicago Housing Activism Through an Environmental Lens. Issue 2 (3rd April 2017) - Young, Lisa J.; Subramaniam, Mangala
ABSTRACT: This article integrates the key concept of oppositional consciousness from social movement theory with the broader notion of community work to argue for understanding the environmental activism of African Americans. Oppositional consciousness developed through community work can significantly challenge dominant ideologies pertaining to environment-related advantages, which the authors refer to as "eco-critical consciousness." Arguing that housing inequality is an integral part of environmental concerns, the authors show that not only did African Americans care about the environmental integrity of their communities, they also took measures to resolve some of the ways environmental degradation affected their health. Using archival information from the Chicago Defender, the authors show that African Americans have consistently challenged conditions of housing discrimination and livability, revealing an intersectional understanding of environmental issues. The analysis reveals the actions, agency, and legacies made by early black Chicagoans on environmental history.